Impact of anesthesia strategy and valve type on clinical outcomes after transcatheter aortic valve replacement - Feistritzer, Hans-Josef; Kurz, Thomas; Stachel, Georg; Hartung, Philipp; Lurz, Philipp; Eitel, Ingo; Marquetand, Christoph; Nef, Holger; Doerr, Oliver; Vigelius-Rauch, Ursula; Lauten, Alexander; Landmesser, Ulf; et al. (Journal of the American College of Cardiology, 2021)
Background - The randomized SOLVE-TAVI (compariSon of secOnd-generation seLf-expandable vs. balloon-expandable Valves and gEneral vs. local anesthesia in Transcatheter Aortic Valve Implantation) trial compared newer-generation self-expanding valves (SEV) and balloon-expandable valves (BEV) as well as local anesthesia with conscious sedation (CS) and general anesthesia (GA) in patients undergoing transfemoral transcatheter aortic valve replacement (TAVR). Both strategies showed similar outcomes at 30 days. - Objectives - The purpose of this study was to compare clinical outcomes during 1-year follow-up in the randomized SOLVE-TAVI trial. - Methods - Using a 2 × 2 factorial design 447 intermediate- to high-risk patients with severe, symptomatic aortic stenosis were randomly assigned to transfemoral TAVR using either the SEV (Evolut R, Medtronic Inc., Minneapolis, Minnesota) or the BEV (Sapien 3, Edwards Lifesciences, Irvine, California) as well as CS or GA at 7 sites. - Results - In the valve-comparison strategy, rates of the combined endpoint of all-cause mortality, stroke, moderate or severe paravalvular leakage, and permanent pacemaker implantation were similar between the BEV and SEV group (n = 84, 38.3% vs. n = 87, 40.4%; hazard ratio: 0.94; 95% confidence interval: 0.70 to 1.26; p = 0.66) at 1 year. Regarding the anesthesia comparison, the combined endpoint of all-cause mortality, stroke, myocardial infarction, and acute kidney injury occurred with similar rates in the GA and CS groups (n = 61, 25.7% vs. n = 54, 23.8%; hazard ratio: 1.09; 95% confidence interval: 0.76 to 1.57; p = 0.63). - Conclusions - In intermediate- to high-risk patients undergoing transfemoral TAVR, newer-generation SEV and BEV as well as CS and GA showed similar clinical outcomes at 1 year using a combined clinical endpoint. (SecOnd-generation seLf-expandable Versus Balloon-expandable Valves and gEneral Versus Local Anesthesia in TAVI [SOLVE-TAVI]; NCT02737150)